A Class of New Permutation Polynomials over F2n - Qian Liu; Ximeng Liu; Jian Zou (Journal of Mathematics)
In this paper, according to the known results of some normalized permutation polynomials with degree 5 over F2n, we determine sufficient and necessary conditions on the coefficients b1,b2∈F2n2 such that fx=x3x¯2+b1x2x¯+b2x permutes F2n. Meanwhile, we obtain a class of complete permutation binomials over F2n.